Clarity and obscurity : a study in textual communication of the relation between sender, parable and receiver in the synoptic Gospels - Du Plessis, Johannes Gysbertus (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 1985.